1968
DOI: 10.1071/bi9680483
|View full text |Cite
|
Sign up to set email alerts
|

Studies of the Distribution and Source of Enzymes in Mammalian Semen

Abstract: SummarySuccinate dehydrogenase (SDH), lactate dehydrogenase (LDH), glutamateoxaloacetate transaminase (GOT), and acid and alkaline phosphatase are present in ram, bull, dog, rabbit, and human semen but the concentrations differ from one species to another. Amylase is found in the semen of all these species except the ram, and glucose·6-phosphate dehydrogenase (GDH) in all except the bull.Studies of the ram and bull showed that if a particular enzyme is present in whole semen, it occurs in both the spermatozoa … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0

Year Published

1968
1968
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 7 publications
3
27
0
Order By: Relevance
“…Glucose and lactate were estimated in protein-free extracts of the spermatozoal suspension at the beginning and end of all metabolic studies by procedures previously described (Murdoch and White 1968). The 14C02 produced by the spermatozoa from D-[l_14C]-and D-[6-14C]glucose was assayed as Ba14C03 by the procedure of Annison and White (1961).…”
Section: (D) Analytical Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Glucose and lactate were estimated in protein-free extracts of the spermatozoal suspension at the beginning and end of all metabolic studies by procedures previously described (Murdoch and White 1968). The 14C02 produced by the spermatozoa from D-[l_14C]-and D-[6-14C]glucose was assayed as Ba14C03 by the procedure of Annison and White (1961).…”
Section: (D) Analytical Methodsmentioning
confidence: 99%
“…Absence of Bicarbonate Hamner and Williams (1964) and Murdoch and White (1968) have shown that bicarbonate is the factor in tubal and uterine fluids stimulating spermatozoal metabolism. It was of interest, therefore, to study the metabolism of spermatozoa after storage in the presence of bicarbonate to see if it would produce a response similar to that obtained with oviduct and uterine fluids in experiment 1.…”
Section: (C) Experiments 3: Metabolism Of Labelled Glucose After Storamentioning
confidence: 99%
See 3 more Smart Citations